Differential transcriptome analysis of the disease tolerant Madagascar–Malaysia crossbred black tiger shrimp, Penaeus monodon hepatopancreas in response to acute hepatopancreatic necrosis disease (AHPND) infection: inference on immune gene response and interaction - Soo, Tze Chiew Christie; Devadas, Sridevi; Mohamed Din, Mohamed Shariff; Bhassu, Subha (BMC, 2019)
Background: Penaeus monodon is the second most widely cultured marine shrimp species in the global shrimp aquaculture industry. However, the growth of P. monodon production has been constantly impaired by disease outbreaks. Recently, there is a lethal bacterial infection, known as acute hepatopancreatic necrosis disease (AHPND) caused by Vibrio parahaemolyticus AHPND strain (Vp AHPND), which led to mass mortalities in P. monodon. Unfortunately, there is still insufficient knowledge about the underlying immune response of P. monodon upon AHPND infection. The present study aims to provide an insight into the antibacterial immune response elicited by P. monodon hepatopancreas towards AHPND infection. Methods: We have employed high-Throughput RNA-Seq technology to uncover the transcriptome changes of P. monodon hepatopancreas when challenged with Vp AHPND. The shrimps were challenged with Vp AHPND through immersion method with dissected hepatopancreas samples for the control group (APm-CTL) and treatment group at 3 (APm-T3), 6 (APm-T6), and 24 (APm-T24) hours post-AHPND infection sent for RNA-Seq. The transcriptome de novo assembly and Unigene expression determination were conducted using Trinity, Tgicl, Bowtie2, and RSEM software. The differentially expressed transcripts were functionally annotated mainly through COG, GO, and KEGG databases. Results: The sequencing reads generated were filtered to obtain 312.77 Mb clean reads and assembled into 48662 Unigenes. Based on the DEGs pattern identified, it is inferred that the PAMPs carried by Vp AHPND or associated toxins are capable of activating PRRs, which leads to subsequent pathway activation, transcriptional modification, and antibacterial responses (Phagocytosis, AMPs, proPO system). DAMPs are released in response to cell stress or damage to further activate the sequential immune responses. The comprehensive interactions between Vp AHPND, chitin, GbpA, mucin, chitinase, and chitin deacetylase were postulated to be involved in bacterial colonization or antibacterial response. Conclusions: The outcomes of this research correlate the different stages of P. monodon immune response to different time points of AHPND infection. This finding supports the development of biomarkers for the detection of early stages of Vp AHPND colonization in P. monodon through host immune expression changes. The potential genes to be utilized as biomarkers include but not limited to C-Type lectin, HMGB1, IMD, ALF, serine proteinase, and DSCAM. © 2019 The Author(s).